(untitled) (PETITUM, 2022)
ABSTRACT: This scientific article was written to find out and examine the legal responsibility of the perpetrators of planting marijuana, in particular to find out how the criminal sanctions are if someone cultivates marijuana plants. The type of observation method used in this study uses the normative method, namely legal research which refers to the norms of the laws and regulations that use secondary data types with primary legal materials Law Number 35 of 2009 concerning Narcotics. Secondary materials (Journals and books About Narcotics). Criminology is a science where it discusses the causes and effects of the emergence of a crime and the events that influence the process of overcoming the crime that occurred. Cannabis plants are plants that are included in the type of Narcotics Group I. The factors that become a factor in the abuse of cannabis cultivation are internal factors and external factors. The eradication of narcotics trafficking is stated in Articles 111 to 126, while narcotics abuse is contained in Articles 127 - 128. This is why it needs the same attention as Articles 111 to 126 of Law Number 35 of 2009. ABSTRAK: Artikel ini ditulis dengan tujuan guna mengetahui dan mengkaji pertanggungjawaban hukum atas pelaksana penanaman ganja, khususnya untuk mengetahui bagaimana sanksi pidana apabila seseorang melakukan penanaman tanaman ganja. Jenis metode observasi dalam pelaksanaan penelitian menggunakan metode normatif, ialah penelitian hukum di mana merujuk pada norma-norma pada peraturan undang-undang yang memakai bahan hukum primer dengan jenis data sekunder yaitu Undang-undang Nomor 35 Tahun 2009 mengenai Narkotika. Data sekunder (Jurnal serta buku mengenai Narkotika). Kriminologi adalah sebuah ilmu pengetahuan dengan topik utama mengenai penyebab dan akibat terciptanya tindak kriminal serta kejadian yang ikut mempengaruhi proses mengatasi kejahatan yang terjadi. Tanaman ganja termasuk dalam tanaman narkotika dengan kelas Golongan I. Adapun yang menjadi faktor penyalahgunaan penanaman ganja adalah factor internal dan factor eksternal. Pemberantasan pengedaran narkotika dikemukakan pada pasal 111 hingga pasal 126, sedangkan penyalahgunaan narkotika terdapat pada pasal 127 - pasal 128, sebabnya butuh mendapatkan perhatian yang sama dengan pasal 111 hingga pasal 126 UU Nomor 35 Tahun 2009.